Malaysian parlimentary election. - Universiti Putra Malaysia, Research Management Centre (Research Management Centre, Universiti Putra Malaysia, 2011)
Results of the 2008 general election caught many analysts and the people at large by surprise. It was totally unexpected that the National Front (NF) would be denied its two-third majority that the ruling coalition has been securing since the first general election held in 1964 after the formation of Malaysia in 1963. Since then, the NF was able to regain its supremacy by winning a two-third majority in the federal parliament until 2008. That therefore makes the 2008 general election the country’s 11th general election held. However, in between these general elections, the ruling NF coalition merely lost one or two states, as it did in the Malay heartland of Kelantan (1990, 1995, 1999, 2004) and Terengganu (1999) as well as the former crown colony of Sabah (1984, 1985, 1990 and 1994). Therefore, when the coalition failed to secure a two-third majority in the 2008 general election and at the same time lost four additional states to a loose electoral pact of the Malay-led PKR (Parti Keadilan Rakyat [Peoples’ Justice Party]), the Islamic based PAS (Pan Islamic Party) and the Chinese dominated DAP (Democratic Action Party), shock waves were felt by all parties across the nation.